Reds in Beds: The Communist Party of Canada and the Politics of Reproduction, 1920-1970 - Beswick, Lorne (Queen's University, 2017)
In the early twentieth-century, the Communist Party of Canada (CPC) initially hesitated to discuss the politics of reproduction as a means of easing material inequity for women and men of the working class. Nevertheless, over five decades, this topic appeared often in the CPCs official and unofficial publications, illustrating a sustained interest in the taboo subject. My thesis draws upon archival materials, communist and mainstream newspapers, and medical periodicals to survey contemporary opinions of birth control, abortion, eugenics, juvenile delinquency, venereal disease, and state medicine. Using the lens of left-politics, these topics are contextualized with reference to the extant literature on the histories of politics, sex, reproduction, labour, and medicine in Canada and beyond. Far from being confined to a few secretive individuals, the militant left engaged a dense network of activists who took stock of the social as well as physical reproduction of the nation. Often their interests appeared indistinguishable from the mainstream, and occasionally overlapped with those of their right-leaning opponents. The CPC unfailingly argued for an understanding of sex and reproduction that reflected its Marxist worldview. Some multi-generational discussions were so durable that they would outlast and outgrow the militant left to emerge within the rhetoric of a multitude of Canadian liberation groups by the late sixties and early seventies. I argue that investigation of the politics underwriting the ideas of the CPC and its ideology of a healthy, socialized body politic, elucidates complexities in the formation of mainstream Canadian approaches to sex, reproduction, and health.